2012
DOI: 10.1089/lap.2012.0113
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Laparoscopic Liposuction for Large Adrenal Myelolipomas: A Report of Nine Cases

Abstract: Retroperitoneal laparoscopic liposuction with suction units is safe and effective for resection of relatively large adrenal myelolipomas. Deflation and shrinkage of the tumor make the operation safer and easier without affecting its pathological diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
0
11
0
4
Order By: Relevance
“…described a retroperitoneal approach for operating large myelolipomas by a technique including liposuction [67]. Two reports demonstrated that if a myelolipoma ruptures, transcatheter arterial embolization using gelatin sponge particles can solve retroperitoneal bleeding from the tumor, and can delay the definitive tumor removal to an elected operation [68,69].…”
Section: Clinical Managementmentioning
confidence: 99%
“…described a retroperitoneal approach for operating large myelolipomas by a technique including liposuction [67]. Two reports demonstrated that if a myelolipoma ruptures, transcatheter arterial embolization using gelatin sponge particles can solve retroperitoneal bleeding from the tumor, and can delay the definitive tumor removal to an elected operation [68,69].…”
Section: Clinical Managementmentioning
confidence: 99%
“…Cistička građa tumora je karakterističnija za benignu promjenu, dok solidna za maligne tumore. Solidni tumori imaju češću incidencu od cističnih i mješovitih [5].…”
Section: Diskusijaunclassified
“…54 It has been reported as well that def lation and shrinkage of relatively large adrenal myelolipomas with retroperitoneal laparoscopic liposuction can make laparoscopic en bloc tumor resection safer and easier without affecting its pathological diagnosis. 55 The concept of liposuction def lation is very appealing and may potentially be extended to minimally invasive ablation for other conditions.…”
Section: Insulin-induced Lipohypertrophy and Hiv-associated Cervicodomentioning
confidence: 99%